The roles of data analytics knowledge on relationship between total quality management and university performance in Pakistan - Khan, Muhammad Adnan (2023)
The objective of this study was to examine the relationship between Total Quality Management, Data Analytics Knowledge, and university performance in higher educational institutes of Pakistan. The Pakistan Higher Education Commission (HEC) oversees the country's general operations and the quality of higher education. Nevertheless, it has yet to improve university performance. Therefore, to achieve great university performance in the higher education sector, it should focus on soft total quality management practices (STQM practices) and hard total quality management practices (HTQM practices). STQM practices included top management, human resource and customer focus. Meanwhile, HTQM practices included benchmarking, continuous improvement, and process management and data analytics knowledge was used as a mediator variable. Meanwhile, university performance is derived from academic and non-academic items. The resource-based view and socio-technical system theory is used as underpinning theory in this study. Based on the theoretical framework, nineteen hypotheses were developed and tested. The methodology of the study is a quantitative and cross-sectional survey and respondents were chosen from middle and lower-middle management of both public and private universities in Pakistan. Simple random sampling was applied for the selection of the respondents. The hypotheses of the study were tested, including the data screening process, descriptive analyses, assessment of the measurement model, and assessment of the structural model. Current research proposed thirteen direct relationships, of which ten were accepted, and three were rejected. Moreover, data analytics knowledge has shown a significant mediating effect. This study provides a theoretical contribution to the resource-based theory and sociotechnical system theory by expanding the total quality management, data analytics knowledge, and university performance nexus. Furthermore, this research provides recommendations and information to both university top management and Pakistan HEC, particularly in derived total quality management and data analytics knowledge for sustaining university performance.